Revisit the Dynamic Portfolio Formation Between Gold and Stocks in Indonesia in The Period Before and During the COVID-19 Pandemic - Ashalia Fitri Yuliana; Robiyanto Robiyanto (Journal of Accounting and Strategic Finance, 2022)
This research aims to review the formation of the dynamic portfolio of individual stocks and gold using the DCC-GARCH and ADCC-GARCH analysis techniques in the periods before and during the COVID-19 pandemic. This is done so that individual investors and investment managers will be able to apply this method. This research uses data from the period of October 2019 - September 2020 with a research sample of nine stocks that are included in the IDX-30. The results showed that the DCC-GARCH analysis technique before the COVID-19 pandemic and the performance of the dynamic portfolios that were unhedged and hedged had no difference. This is due to the conditions in the period before the COVID-19 pandemic which still tended to be stable, thus, no safe-haven asset is needed. Meanwhile, in the period during the COVID-19 pandemic, using the DCC-GARCH analysis technique, there were differences because conditions have started to fluctuate in uncertainty which resulted in the need for safe-haven assets. On the other hand, using the ADCC-GARCH analysis technique on the periods before and during the COVID-19 pandemic, the performance of the dynamic portfolios that were unhedged and hedged showed a difference. Because the ADCC-GARCH technique is able to see asymmetric volatility for the future, adding gold to a portfolio can reduce risk when there is uncertainty. This research also found that the ADCC-GARCH technique had better performance than the DCC-GARCH technique.